Fecundity changes in Macrobrachium rosenbergii (de Man) during egg incubation - Jee, Ang Kok; Kok, Law Yean (John Wiley & Sons, 1991)
Abstract. For a study of the fecundity of Macrobrachium rosenbergii, a total of 117 berried females were sampled from ponds. Fecundity was found to vary from 1216 to 89747 eggs for prawns measuring 9.0cm to 15.8cm total length and weighing 6.22 to 45.80g. The relationship between fecundity (EN) and total length (TL) was found to be EN = 0.001876 TL6.3617. The average egg number/g total body weight for prawns having orange, yellow and grey eggs was 1132.7 ± 484.1,766.4 ± 524.3 and 745.5 ± 487.2, respectively, a decrease of 32.3% when orange eggs became yellow and 34.3% when they turned grey. This decrease was probably due to unfertilized eggs dropping off and some eggs being eaten by the brooders during the incubation period. Egg numbers/g egg weight were found to be 11360.1 ± 1642.1,10715.7 ± 2725.3 and 8634.0 ± 1892.3 for orange, yellow and grey eggs, respectively. When compared to orange eggs, yellow eggs were slightly heavier (6%), but grey eggs were significantly heavier by 31.6%. The increase in the weight of the grey eggs can be explained by the elongation of fully formed organs and appendages by about 17 days post fertilization.